Integration of physico-chemical and enzymatic pretreatments of oil palm biomass for enhancement of glucose production - Ahmad Rizal, Nur Fatin Athirah (2018)
Oil palm empty fruit bunch (OPEFB) and oil palm mesocarp fiber (OPMF) are lignocellulosic biomass that abundantly generated in palm oil mills. However, the presence of these oil palm wastes has created a major disposal problem. Current treatment is either by mulching at the plantation of dumping at side of the mill. Since these materials are rich in carbohydrate the OPEFB and OPMF have been widely reported as suitable raw materials to produce fermentable sugars. However, the presence of lignin and hemicellulose in their composition hinders the access of cellulase to hydrolyze cellulose. Effective pretreatments are required to reduce the recalcitrance of lignocellulosic structures and improve the fermentable sugars production. Combination of physico-chemical and biological pretreatment was proposed to enhance glucose production from OPEFB and OPMF.